2020
DOI: 10.1155/2020/5603580
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Resistance Training Induced Modifications in the Left Ventricle Proteome Independent of Offspring Diet

Abstract: Ancestral obesogenic exposure is able to trigger harmful effects in the offspring left ventricle (LV) which could lead to cardiovascular diseases. However, the impact of the father’s lifestyle on the offspring LV is largely unexplored. The aim of this study was to investigate the effects of 8 weeks of paternal resistance training (RT) on the offspring left ventricle (LV) proteome exposed to control or high-fat (HF) diet. Wistar rats were randomly divided into two groups: sedentary fathers and trained fathers (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(29 citation statements)
references
References 57 publications
(70 reference statements)
1
28
0
Order By: Relevance
“…In animals models, adiponectin-deficient mice demonstrated a near-normal insulin sensitivity when fed with control diet, however, developed insulin resistance in skeletal muscle after 2 weeks of exposure to HF diet (Maeda et al, 2002). In the same experimental model, the area under the curve of blood glucose did not reveal significant differences between offspring groups (de Sousa Neto et al, 2020), which may be related to Wistar rats not responding pronouncedly to an HF diet when compared to other mouse strains. Future studies will be required to evaluate the link between changes of adiponectin and glucose uptake by tenocytes besides glucose transporters.…”
Section: Discussionmentioning
confidence: 88%
“…In animals models, adiponectin-deficient mice demonstrated a near-normal insulin sensitivity when fed with control diet, however, developed insulin resistance in skeletal muscle after 2 weeks of exposure to HF diet (Maeda et al, 2002). In the same experimental model, the area under the curve of blood glucose did not reveal significant differences between offspring groups (de Sousa Neto et al, 2020), which may be related to Wistar rats not responding pronouncedly to an HF diet when compared to other mouse strains. Future studies will be required to evaluate the link between changes of adiponectin and glucose uptake by tenocytes besides glucose transporters.…”
Section: Discussionmentioning
confidence: 88%
“…Some reports showed that voluntary wheel running in the fathers suppresses the detrimental effects of a paternal high fat (HF) diet on offspring, reducing the negative effects on fat mass and glucose uptake in different skeletal muscles, which could be an important intervention to prevent type 2 diabetes 21,25 . Current advances have introduced new opportunities to map the complex epigenetic mechanisms regarding paternal exercise 20,25,26 . Modifications in sperm provide a potential molecular basis to explain the contribution of the father's lifestyle 27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…These epigenetic changes modulate cellular plasticity in the extra‐uterine environment, and might provide a survival advantage by regulating the differential genes that encode proteins involved in energy metabolism 25 . Sperm‐derived non‐coding RNA modifications induce changes in the chromatin structure and recruit transcriptional cofactors to DNA to regulate gene expression or genome activity, which might alter offspring proteomes 20 . These changes may reprogram the translational machinery, resulting in embryonic morphogenesis changes, and, subsequently, organ and tissue development in the offspring 27,28 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations